The Prevalence Pediatric Patients Attending in A Tertiary care Hospital in Dhaka, Bangladesh (Bangladesh Journal of Medical Science, 2024)
Introduction The incidence of skin conditions in young people typically varies between nations and within a single nation’s regions based on social, economic, racial, and environmental factors. A significant public health issue is the morbidity that skin diseases cause in children. There is a dearth of research on this pediatric issue in our nation, which is either centered on a condition, a community, or a particular population group. Objective To evaluate the dermatological complaints of the pediatric patients attending a dermatology outpatient department in a tertiary care hospital. Materials And Methods We retrospectively analyzed a total of 2472 pediatric patients who were in age range 0-18 years and came to the OPD of dermatology & venereology department of Ibn Sina Medical College Hospital, Dhaka, Bangladesh, over a period of 1½ year from January, 2020 to June, 2021. Data were collected on special proforma and analyzed with appropriate method. Results Among 2472 patients 1157 (46.8%) were male and 1315 (53.2%) were female and most of the patients belonged to the age group 12-18 year (52.6%). Male female ratio was 0.88:1. All diseases were broadly classified into noninfectious (71.2%) and infectious dermatoses (28.8%). Dermatitis (38.9%), infections (28.8%) and acne (14.44%) came out to be the top most common cause for OPD attendances. For the specific skin diseases, 20.1% were atopic dermatitis, 14.44% were acne, and 11.8 % were fungal infections. Atopic dermatitis was the most common condition below 12 years of age. In 12-18 years of age group, the most common condition was acne; females were more affected than males. Among the viral infections, wart was the most common (22.1%). Conclusion Atopic dermatitis was found to be the most common noninfectious disease and fungal infection was the most common infectious disease in all age groups and genders.Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1054-1059